437 IN VITRO SENSITIVITY OF HSV-TK TRANSDUCED CELLS TO GANCICLOVIR, ACYCLOVIR, AND FOSCARNET. (1st January 2006) - Methangkool, E.; Blumenthal, M.; Kohn, D.
Abstract : Gene therapy is a promising alternative to conventional therapies for patients affected with congenital immune deficiencies. Although retroviral vectors are an effective means to deliver normal versions of the affected genes to the DNA of hematopoietic stem cells (HSCs), their insertion into DNA is random and may precipitate leukemic events should they insert near proto-oncogenes. A potential approach to this problem is the use of "suicide genes, " a second gene added to the therapeutic retroviral vector that can be used to eliminate cells if they cause leukemia. One candidate is the herpes simplex virus thymidine kinase (HSV-TK) gene. If patients undergoing gene therapy develop leukemia, they can be administered the prodrug ganciclovir, which will be activated by the thymidine kinase protein expressed by the transduced leukemic cells. Ganciclovir will eliminate any cells expressing HSV-TK while leaving other cells intact. However, immune-deficient patients undergoing treatment with the therapeutic retroviral vector and suicide gene can subsequently acquire herpes virus infections. These patients cannot be treated with antiviral nucleosides such as ganciclovir or acyclovir because they will kill off the corrected cells. Foscarnet, a drug used to treat ganciclovir- and acyclovir-resistant herpes infections, may be an alternative treatment for these patients. We evaluated the in vitro sensitivity of transduced TK cell lines to ganciclovir, acyclovir, and foscarnet using a 5-day cytotoxicity assay with varying concentrations of each drug. Cell lines remained near 100% viability in the presence of foscarnet while demonstrating low viability in the presence of ganciclovir and acyclovir. The ability of these cell lines to survive in the presence of foscarnet improves the therapeutic value of the suicide gene approach to gene therapy as it may provide viable treatment option for patients who acquire herpes infections.